Integrated English Language Development : Supporting English Learners Across the Curriculum. - Mora-Flores, Eugenia (Professional Resources Ser., 2018)
This powerful resource defines and supports the implementation of Integrated English Language Development (I-ELD) and provides research-based instructional strategies to immerse students in content while promoting oral and written language development.